Kendala Yang Dihadapi Penerjemah dan Pranata Humas Dalam Pelaksanaan Tugas Dan Fungsinya - Febrina Natalia; Dewi Yuliyanti (Jurnal Penelitian Pers dan Komunikasi Pembangunan, 2020)
This study aims to determine what difficulties met by government translator and government public relations officers in carrying out their duties and function in the Bureau of Leadership Administration, Regional Secretariat of Central Kalimantan Province from data analysis obtained from questionnaires, observations and related literature studies. The method used in this research is descriptive; the researchers describe the phenomena arisen from questionnaire data which are the answers of respondents filled by the government translator and government public relations officers in the Bureau of Leadership Administration, Regional Secretariat of Central Kalimantan Province. This data analysis is also supported by observation and study of other related literature. This study shows there are several difficulties and overlaps found in the tasks division between government translator and government public relations officers, especially in the field of translation, government relations and public information. Understanding this issue, it is hoped that both government translator and government public relations officers master basic knowledge and competencies related to their job descriptions as discussed in this research. In addition, officials at the structural level are also expected to better understand the duties and function of government translator and government public relations officers so that in coordination and implementation of their tasks, their role can be more optimal. Keywords: government, translator, public relations ABSTRAK Penelitian ini bertujuan untuk mengetahui kendala apa saja yang dihadapi oleh penerjemah dan pranata humas dalam pelaksanaan tugas pokok dan fungsinya khususnya dalam kegiatan penerjemahan, kehumasan dan informasi melalui analisis data yang diperoleh dari kuesioner, observasi dan studi literatur. Metode yang digunakan dalam penelitian ini bersifat deskriptif yaitu peneliti menjabarkan fenomena yang muncul berdasarkan data kuesioner yaitu jawaban responden yang diisi oleh pranata humas dan penerjemah di Biro Administrasi Pimpinan, Sekretariat Daerah Provinsi Kalimantan Tengah. Analisis data ini juga didukung dengan observasi dan studi literatur terkait lainnya. Kajian ini menunjukkan beberapa kendala dan tumpang tindih serta ketimpangan pembagian tugas antara penerjemah dan pranata humas khususnya dalam kegiatan penerjemahan, kehumasan dan informasi di Biro Administrasi Pimpinan, Sekretariat Daerah Provinsi Kalimantan Tengah. Memahami hal tersebut, diharapkan penerjemah dan pranata humas menguasai pengetahuan dan kompetensi dasar terkait uraian tugas dimaksud. Selain itu, pejabat jenjang struktural diharapkan juga lebih memahami tugas pokok dan fungsi penerjemah dan pranata humas sehingga dalam koordinasi dan pelaksanaan tugas, peran keduanya dapat lebih optimal Kata kunci: pemerintah, penerjemah, pranata humas